Actual activation energy of the electroreduction of palladium(II) iminodiacetate complexes - Kublanovsky, V.S.; Nikitenko, V.M. (Reports of the National Academy of Sciences of Ukraine, 2017)
The actual and true activation energies of the electroreduction of palladium(II) bis-iminodiacetate comp lexes have been calculated. A method is proposed for the calculation of the actual activation energy of the electrode process controlled by a mixed kinetics from the activation energy of diffusion, the electron-transfer reaction, and the ratio of surface and bulk concentrations of potential-determining ions in the solution under investigation. There is a good agreement between the calculated and experimentally determined values of the actual activation energy of the electrode process. The dependence of the actual activation energy on the electrode process overpotential has been studied.